Adolescents' Perceptions of Popularity-Motivated Behaviors, Characteristics, and Relationships in Cyberspace and Cyber Aggression: The Role of Gender - Wright, Michelle F (Cyberpsychology, behavior and social networking, 2017)
Research is increasingly revealing that adolescents utilize electronic technologies to promote and/or maintain their social standing among their peer group. Little is known about whether adolescents' perceptions of popularity-motivated behaviors, characteristics, and relationships in cyberspace are associated with popularity-motivated cyber relational aggression. It is also unclear how gender might impact these associations, especially considering that adolescent girls and boys differ in regard to the type of behaviors, characteristics, and relationships they believe contribute to popularity. To this end, this study examined the potential moderating effect of gender on the association between adolescents' perceptions of popularity-motivated behaviors, characteristics, and relationships in cyberspace and their engagement in popularity-motivated cyber relational aggression over 1 year, from seventh to eighth grade. There were 217 eighth graders (51 percent female; M age = 12.13) from three middle schools in a large Midwestern city in the United States included in this research. They completed questionnaires on their popularity-motivated behaviors, characteristics, and relationships in cyberspace and their perpetration of popularity-motivated cyber relational aggression during the seventh grade. One year later, they completed the perpetration of popularity-motivated cyber relational aggression questionnaire. The results revealed that the association between popularity-motivated behaviors, characteristics, and relationships in cyberspace and the perpetration of popularity-motivated cyber relational aggression was stronger for girls, while such an association was not found for boys. These findings indicate the importance of considering cyberspace as an environment in which adolescents can enhance their social standing among peers from their school.
Keywords: Male; internet; percepce; Adolescent; Perception; relational aggression; popularity; vyrovnaná skupina; Peer Group; Motivation; mužské pohlaví; genderová identita; průzkumy a dotazníky; cyber aggression; Internet; mladiství; impression management; Schools; školy; lidé; motivace; ženské pohlaví; Humans; adolescence; Gender Identity; psychologický odstup; Aggression; Female; Surveys and Questionnaires; agrese; adolescent; Psychological Distance